Warming triggers stomatal opening by enhancement of photosynthesis and ensuing guard cell CO2 sensing, whereas higher temperatures induce a photosynthesis-uncoupled response - Pankasem, Nattiwong (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.